ABCC8 EXON 16-3 C>T POLYMORPHISM IS ASSOCIATED WITH INSULIN SECRETION IN PATIENTS WITH TYPE 2 DIABETES IN YOGYAKARTA - Johana puspasari Dwi Pratiwi (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background ABCC8 is a gene encoding the SUR1 subunit of the KATP Channel which plays a central role in insulin secretion from the beta cell, hence its potential as the candidate risk gene in the development of type 2 Diabetes Mellitus (DM type 2). the polmorphism of ABCC8 exon 16 -3 C>T has been investigated in various populations with inconsistent result. Therefore, this study aimed to explore the association of the polymorphism with DM type 2 in Yogyakarta population. Method a number of 40 patients with DM type 2 and 44 patients without DM type 2 were recruited as case and control subjects, respectively. the polymorphism was genotyped using PCR-RFLP. The association between insulin secretion and the polymorphism was analyzed with ANOVA and Post Hoc Test. Chi-square and odds ratio were employed to determine whether the polymorphism was a risk of DM type 2. Results There was a significant difference between CC and CT genotypes among subjects with DM type 2 (p=0,005). Fasting insulin concentration exhibited a significant difference between CC and TT genotypes among DM type 2 subjects (p=0,013). Allele T frequency was found to be 0,45 among DM type 2 subjects and 0,48 among non DM subjects, there was no significant difference of allele T frequency between DM type 2 and non DM subjects (p=0,723, OR=0,90, CI: 0,49-1,65). Conclusion ABCC8 exon 16 -3 C>T polymorphism was not associated with DM type 2 prevalency in Yogyakarta population, however the impact of the polymorphism on diabetes pathogenesis in DM type 2 can not be excluded because of the association with insulin secretion in DM type 2 subjects.